2016
DOI: 10.3758/s13421-016-0605-z
|View full text |Cite
|
Sign up to set email alerts
|

Divergent creative thinking in young and older adults: Extending the effects of an episodic specificity induction

Abstract: Recent research has suggested that an episodic specificity induction- brief training in recollecting the details of a past experience- enhances divergent creative thinking on the Alternate Uses Task (AUT) in young adults without affecting performance on tasks thought to involve little divergent thinking, but the generalizability of these results to other populations and tasks is unknown. The present experiments examined whether effects of an episodic specificity induction extend to older adults and a different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
100
9
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 115 publications
(135 citation statements)
references
References 52 publications
15
100
9
11
Order By: Relevance
“…The episodic specificity induction did not alter the overall relationship between internal and external details, meaning that if the generation of external details is entirely a secondary by-product of amount of internal details (or vice versa), a reciprocal effect between the two should be observed. However, it has previously been shown that in most experiments the episodic specificity induction increases internal details, but does not decrease external details (Madore et al, 2014; Madore, Jing, et al, 2016; Madore & Schacter, 2014, 2016; Madore, Szpunar, Addis, & Schacter, 2016; but see Jing, Madore, & Schacter, 2016; Madore, Addis, & Schacter, 2015). Furthermore, different types of future imaginations can alter the amount of internal details generated, with no concurrent effects on external details (de Vito, Neroni, Gamboz, Della Sala, & Brandimonte, 2015; see also Neroni, Gamboz, De Vito, & Brandimonte, 2016), and age-related decreases in internal details have been reported even when the number of external details does not differ with age (Madore & Schacter, 2014; Zavagnin et al, 2016).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The episodic specificity induction did not alter the overall relationship between internal and external details, meaning that if the generation of external details is entirely a secondary by-product of amount of internal details (or vice versa), a reciprocal effect between the two should be observed. However, it has previously been shown that in most experiments the episodic specificity induction increases internal details, but does not decrease external details (Madore et al, 2014; Madore, Jing, et al, 2016; Madore & Schacter, 2014, 2016; Madore, Szpunar, Addis, & Schacter, 2016; but see Jing, Madore, & Schacter, 2016; Madore, Addis, & Schacter, 2015). Furthermore, different types of future imaginations can alter the amount of internal details generated, with no concurrent effects on external details (de Vito, Neroni, Gamboz, Della Sala, & Brandimonte, 2015; see also Neroni, Gamboz, De Vito, & Brandimonte, 2016), and age-related decreases in internal details have been reported even when the number of external details does not differ with age (Madore & Schacter, 2014; Zavagnin et al, 2016).…”
Section: Discussionmentioning
confidence: 94%
“…Madore et al (2014) also examined generation of details in a non-episodic picture description task, as well as the influence of an episodic specificity induction – brief training in recollecting specific details of past experiences – on internal and external detail production. They found that for both younger and older adults, the specificity induction selectively enhanced internal details during descriptions of remembered and imagined events, while having no influence on external output or performance on the picture description task (see also Madore, Jing, & Schacter, 2016; Madore & Schacter, 2014; Schacter & Madore, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Motivated by previous behavioral work highlighting the relationship between episodic future simulation and divergent thinking (Addis et al, 2016; Madore, Addis, & Schacter, 2015; Madore, Jing, & Schacter, 2016), we explored whether our behavioral and BOLD variables were associated with this form of cognitive flexibility (as measured by the AUT flexibility scores). Our results revealed that AUT flexibility scores were negatively correlated with Congruent-Incongruent difference scores for both plausibility and difficulty ratings.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of older adults have begun to examine adaptive uses of episodic memory in imagination (e.g., Addis et al, 2008), problem solving (Madore and Schacter, 2014; Sheldon et al, 2011), and creativity (Madore et al, 2016), but direct links between these adaptive processes and false memory in aging need to be explored.…”
Section: Further Questions and Considerationsmentioning
confidence: 99%